The preparation of an ultrastable mesoporous Cr(iii)-MOF via reductive labilization. Issue 12 (16th September 2015) - Lian, Xizhen; Feng, Dawei; Chen, Ying-Pin; Liu, Tian-Fu; Wang, Xuan; Zhou, Hong-Cai
Abstract : A novel reductive labilization–metal metathesis method is reported for the synthesis of an ultrastable mesoporous Cr(iii )-MOF. Abstract : Kinetic labilization of the Fe(iii )–O coordination bond in a mesoporous metal–organic framework, PCN-333-Fe(iii ), is realized by the reduction of Fe(iii ) by Cr(ii ). The Fe(ii )–Cr(ii ) metathesis is thus completely achieved followed by this reductive labilization process that generates PCN-333-Cr(iii ). The kinetic inertness of Cr(iii ) provides PCN-333-Cr(iii ) with enhanced chemical stability as well as a broader range of applications compared to those of PCN-333-Fe(iii ). For instance, alkylamine incorporated PCN-333-Cr(iii ) demonstrated significant carbon dioxide uptake while PCN-333-Fe(iii ) lost its crystallinity after alkylamine treatment.